2022
DOI: 10.1155/2022/5810405
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Clinical Comparison of Endoscopic Ultrasonography and CT in Preoperative TN Staging of Esophagogastric Junction Cancer

Abstract: In recent years, the incidence of esophagogastric junction cancer has increased year by year. It is a special type of gastric cancer, with 80% of patients being clinically in the middle and late stages. The traditional treatment methods are extremely ineffective, and the accuracy of preoperative staging is not good enough. At present, the medical treatment for esophagogastric junction cancer mainly adopts surgery and postoperative adjuvant therapy. The current mainstream clinical diagnostic methods of esophago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%